4j-10=-j

Simple and best practice solution for 4j-10=-j equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4j-10=-j equation:


Simplifying
4j + -10 = -1j

Reorder the terms:
-10 + 4j = -1j

Solving
-10 + 4j = -1j

Solving for variable 'j'.

Move all terms containing j to the left, all other terms to the right.

Add 'j' to each side of the equation.
-10 + 4j + j = -1j + j

Combine like terms: 4j + j = 5j
-10 + 5j = -1j + j

Combine like terms: -1j + j = 0
-10 + 5j = 0

Add '10' to each side of the equation.
-10 + 10 + 5j = 0 + 10

Combine like terms: -10 + 10 = 0
0 + 5j = 0 + 10
5j = 0 + 10

Combine like terms: 0 + 10 = 10
5j = 10

Divide each side by '5'.
j = 2

Simplifying
j = 2

See similar equations:

| -8n+6=-10n | | .5x-6=4x+8 | | 8v=9+9v | | 9(3x+5)=8x-7 | | -9+4u=-u+6 | | 15y^3-18y^2+3y= | | -4(3x-8)=2 | | -3-5s=-7-6s | | x+x(.15)=315000 | | -6y+2=4-6y | | f(x)=5x^2-6x+5 | | A=pir^2+2pirh | | X^4-40X^2-33=0 | | 4(3n+1)=6(2n-1) | | 9j=-7+10j | | 24.3=12.4+2a | | -3x-2+1=-7 | | -7g=-2-6g | | 12x^2-16x-6=0 | | -7g=-2-6 | | 12k=-36 | | 16-20x-21-6x=18-6x-12x-1 | | -5y+10=-6y | | 23a+7= | | 9v=10v+9 | | 17-6x+3x-5=x+11+4x | | -3m+10=-4m | | 17-6x+3x-5=x+11 | | 6+16x=17x+2 | | 5h=7h+8 | | 24.3=14.4+2a | | 18a-7= |

Equations solver categories